PERBANDINGAN IPV4 DAN IPV6 DALAM MEMBANGUN JARINGAN LOCAL AREA NETWORK (LAN) - Ulfa, maria (JURNAL ILMIAH MATRIK, 2014)
IP address is also called the identification codes, the computer on the network / internet, each every computer which incircuit to network have to own a IP address in each interface and IP address by self have to be unique because there may not be any computer using same IP address. IPv4 which is equal to 32 bit will difficult to obtain in the future, therefore needed a new development of the IP address, Internet Protocol version 6 (IPv6), known as Internet Protocol Next Generation (IPNG). IPng is a new third layer protocol designed to replace IPv4. The author attempt a comparative study using IPv4 and IPv6 in building a Local Area Network (LAN). This study is expected to be helpful for the users who will make the transition from IPv4 to IPv6.